Концепції та основні ідейні принципи соціального контролю - Яцишин, М.; Яцишин, Н.; Yatsyshyn, M.; Yatsyshyn, N. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Розглядаються аспекти створення соціального механізму взаємодії суб’єктів громадянського суспільства з метою вирішення суспільно значущих завдань правопорядку, основою для розробки якого є соціальний контроль. Автори у соціальному контролі за станом суспільних відносин виділили три найважливіші напрямки, а саме ретроспективний, превентивний і прогнозуючий контроль. Ретроспективний соціальний контроль показує спектр раніше розглянутих проблем, механізм їх вирішення та досягнутий результат. Превентивний соціальний контроль сприяє виробленню у громадян стереотипів поведінки, заснованих на суспільно значущих соціальних нормах The article analyzes the aspects of creating a social mechanism of interaction between the civil society subjects to solve socially significant problems of the rule of law. Social control model is the basis for this mechanism development and improvement. In terms of the public relations social control, the study has identified the three most important fields of it: retrospective, preventive, and prognostic control. Retrospective social control shows the range of previously considered problems, the mechanism of their solution, and the results achieved. This control becomes the basis for a more detailed assessment of the results in combating various offenses. Preventive social control contributes to the development of social behavior stereotypes based on the socially significant social norms, which in the long run, are supposed to help members of a society orientate in different life situations and thus enshrine the moral, ethical, and spiritual experience of social development.
Social Сontrol: Сoncepts and Basic Ideological Principles
Keywords: громадянські інститути; соціальні інститути; соціальний порядок; соціальний контроль; civil institutions; social institutions; social order; social control